Analisis Pengukuran Jarak Objek Dengan Sensor Ultrasonik(HC-SR04) untuk Berbagai Bentuk Objek - Safhira Aulia Nurazizah; Zainatul Khasanah; Risqillah Ayu Puspita S; Moh Avin Annabil (Fakultas MIPA, Universitas Jember, 2024)
This experiment aims to determine the effect of the shape of the object on the distance and reading frequency of the HC-SR04 ultrasonic sensor and how far away the object is captured by the sensor. The method used is the experimental method and data analysis. This method is used to make it easier to obtain data. This experiment was carried out by varying the distance of 10 cm with obstacles (objects) of different sizes from the sensor until the object could not be detected by the sensor. The data obtained is in the form of calculated distances and frequency values. This data is then processed using MS Excel. The results obtained are in the form of analysis tables and graphs. The experimental results show that the distance of the object affects the frequency produced by the HC-SR04 ultrasonic sensor. The farther the object is, the lower the resulting frequency. Variations in object shape also affect the frequency produced by the HC-SR04 ultrasonic sensor. Objects that have a square shape will produce a higher frequency than objects that have a round shape. This research provides information about the influence of distance and variations in object shape on the frequencies produced by the HC-SR04 ultrasonic sensor. This information can be used to improve the accuracy of distance measurements using the HC-SR04 ultrasonic sensor. The largest average error value obtained was 0.13%, namely in experiments using a spherical object with a diameter of 2.5 cm. The smallest average error value obtained was 0.01%, namely in the experiment using a box object measuring 2x3 cm